Traditional Uses, Pharmacology and Phytochemistry of the Medicinal Plant Flueggea virosa (Roxb. ex Willd.) Royle - Christian Bailly (MDPI AG, 2024)
The white berry bush, officially Flueggea virosa (Roxb. ex Willd.) Royle is a medicinal plant distributed throughout tropical areas and traditionally used in Africa, India and China. Root decoctions are used to treat abdominal pain, whereas extracts from the aerial parts serve to treat liver and urinary diseases, inflammatory pathologies and diabetes, among other pathologies. Plant extracts have revealed antiparasitic, antimicrobial, antiepilepsy, antidiabetic, anticancer and analgesic effects. Three main categories of phytochemicals were isolated from F. virosa: polyphenols, with the lead product bergenin; terpenoids, such as the flueggenoids and related podocarpane-type diterpenoids; and many alkaloids derived from securinine and norsecurinine. A remarkable feature of S. virosa is the production of norsecurinine oligomers, including macromolecular tetramers and pentamers, such as fluevirosinines. The most potent anticancer alkaloid in the family is the dimeric indolizidine flueggine B, which was identified as a potential binder to α/β-tubulin dimer, which is a known target for securinine. This review highlights the diversity of phytochemicals identified from S. virosa and the potential therapeutic benefits of dimeric alkaloids. Studies are encouraged to further investigate the therapeutic properties of the lead compounds but also define and finesse the nutritional profile of the edible fruit.